2022
DOI: 10.1126/sciadv.add1757
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency blue-emission crystalline organic light-emitting diodes sensitized by “hot exciton” fluorescent nanoaggregates

Abstract: Sensitizing fluorescent materials is an effective way to maximally use excitons and obtain high-efficiency blue organic light-emitting diodes (OLEDs). However, it is a persistent challenge for present amorphous thin-film OLEDs to improve photon emission under low driving voltage, severely impeding the development of OLED technology. Here, we propose a novel OLED architecture consisting of a crystalline host matrix (CHM) and embedded “hot exciton” nanoaggregates (HENAs), which effectively sensitize blue dopant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 73 publications
3
13
0
Order By: Relevance
“…Additionally, although a typical material system of MADN: DSA‐Ph (3 wt%) was used to fabricate a long‐lifetime blue OLED (T 1/2 = 46 000 h), [ 50 ] it shows evident molecular aggregates and “pinholes” within 20 h at Condition 1 and 20 min at Condition 2. [ 27 ] These results demonstrated superior stability of the CHM‐TADFNA thin film and their potential in realizing OLED with high operational stability.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Additionally, although a typical material system of MADN: DSA‐Ph (3 wt%) was used to fabricate a long‐lifetime blue OLED (T 1/2 = 46 000 h), [ 50 ] it shows evident molecular aggregates and “pinholes” within 20 h at Condition 1 and 20 min at Condition 2. [ 27 ] These results demonstrated superior stability of the CHM‐TADFNA thin film and their potential in realizing OLED with high operational stability.…”
Section: Resultsmentioning
confidence: 93%
“…However, the four devices exhibit comparable current densities, although the device with an NDT of 3.0 nm exhibits a relatively low current density. Based on our previous study, [ 27 ] it was demonstrated that the CHM is the pathway for hole transportation. On the other hand, electrons are directly injected from the cathode due to the deep LUMO of DMAC‐DPS nanoaggregates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic light-emitting diodes (OLEDs) have received tremendous attention since the first demonstration of double-layer structure [1][2][3][4][5][6][7][8][9][10][11][12][13], due to their attractive properties such as light weight, self-emission with highquality color, and availability for fabricating high-resolution display panel. The current level of OLEDs stability at the luminance of ∼2000 cd m −2 enables the successful applications of OLEDs in the important intermissive display fields, e.g., smart phones and watches.…”
Section: Introductionmentioning
confidence: 99%